Réponses

2014-10-29T23:10:46+01:00
A) pour x=2 ; 2(2+3)(4*2 - 2)+(2+3)=2(5)(6)+5=60+5=65
b) expression littérale développée
  A=2(x+3)(4x-2)+(x+3)
    = 2(4x²-2x+12x-6)+x+3
    = 2(4x²+10x-6) +x+3
    = 8x²+20x-12+x+3
 A = 8x²+21x-9
 pour x=2; A=8*2²+21*2-9
                  =32+42-9
                A=32+33
                A=65
c) expression littérale factorisée
  A=2 (x+3)(4x-2)+(x+3)
    =(x+3)[2(4x-2)+1)]
    =(x+3)(8x-4+1)
    = (x+3)(8x-3)
pour x=2 ; A=(2+3)(8*2 -3)
                  =5(16-3)
                  =5*13
                  =65